CRISPR/Cas9-induced Mutation of Sex Peptide Receptor Gene Bdspr Affects Ovary, Egg Laying, and Female Fecundity in Bactrocera dorsalis (Hendel) (Diptera: Tephritidae). Issue 1 (14th January 2023) - Chen, Hao; Sun, Hao; Xie, Junfei; Yao, Zhichao; Zheng, Wenping; Li, Ziniu; Deng, Zhurong; Li, Xiaoxue; Zhang, Hongyu
Abstract: The oriental fruit fly, Bactrocera dorsalis (Hendel) (Diptera: Tephritidae), is an invasive and polyphagous pest of horticultural crops, and it can cause huge economic losses in agricultural production. The rapid development of CRISPR/Cas9 gene editing technology has provided new opportunities for the scientific control of agricultural pests. Here, we explore the applicability of the B. dorsalis sex peptide receptor ( Bdspr ) as a target gene for the CRISPR/Cas9-based sterile insect technique (SIT) in B. dorsalis . We screened two high-efficient single guide RNAs (sgRNAs) for gene editing. The results showed that both mutation efficiency and germline transmission rate were 100% in the surviving G0 females (8/8) from injected embryos, and that 75% of mosaically mutated G0 females (6/8) were sterile. The 50% of heterozygous G1 females (4/8) could not lay eggs; 100% of eggs laid by them could not survive; and 62.5% of individual females (5/8) had abnormal ovaries. These results indicate that Bdspr plays an important role in regulating fertility, egg viability, and ovary development in female B. dorsalis, suggesting that the spr gene can be used for CRISPR/Cas9-based SIT in B. dorsalis.